P8 Tumor-associated B cells in head and neck squamous cell carcinoma (HNSCC). Issue 5 (May 2015) - , .; Schlößer, H.; Thelen, M.; Shimabukuro-Vornhagen, A.; Beutner, D.; von Bergwelt-Baildon, M.
Abstract : Introduction: The immune system plays a role in both the promotion and prevention of tumor development. A precise understanding of the mechanisms by which human immune cell subsets affect tumor biology will be critical for the successful treatment of cancer with immunotherapeutic approaches. To date, little is known about the role that B cells play in cancer pathophysiology. Recent evidence suggests that B lymphocytes can both promote and inhibit the development and progression of tumors. Whether B cells support or hinder tumor growth seems to depend on a variety of factors such as tumor entity, timing, and composition of the B cell subsets. Tumor-infiltrating B cells have been described in a large variety of solid tumors including head and neck squamous cell carcinoma (HNSCC) but there has not been a detailed phenotypic characterization of the different B cell subsets in HNSCC as a first step to further elucidate the impact of B lymphocytes in HNSCC. Materials and methods: We obtained tumor samples, healthy mucosa and peripheral blood from patients with treatment-naive HNSCC and healthy donors. Analysis of immune cell distribution and B cell subsets was performed by flow cytometry and immunohistochemistry. Results: Flowcytometric analyses revealed lymphocytic infiltration in all analyzed HNSCC tumors ( n = 12) and a substantial B cell infiltration in the majority of tumors. Immunohistochemical analysis showed similar results. Subclassification of tumor-infiltrating B cell subsets showed high numbers of activated B cells, antigen-presenting B cells, plasma blasts and memory B cells. Interestingly, an increase in regulatory B cells within the tumors could not be detected. Conclusion: In accordance with previous results we found that there is a marked B cell infiltration in the majority of HNSCC. Our results are indicative of an antigen recognizing B cell phenotype in HNSCC and provide a first comprehensive analysis of the subsets of tumor-infiltrating B cells in HNSCC so far. In murine carcinogenesis models of squamous cell carcinoma a crucial role for B cells has been proposed. If this holds true for human HNSCC as well remains to be evaluated in further studies.